AN OVERVIEW : THE ENVIRONMENTAL IMPACT OF LNG REGASIFICATION SCHEME FOR SUPPLYING DOMESTIC NATURAL GAS - Dwi Anggoro Ismukurnianto (Scientific Contributions Oil and Gas, 2003)
In Order to supply domestic gas demand which will be in shortage in 2004, especially in West Java where most gas consumers, are located LNG regasification scheme is an alternative technology that may be used for transporting gas from other islands to Java.